DETERMINANTS OF FOREIGN DIRECT INVESTMENT (FDI) AND ITS IMPACT ON GNP AND EMPLOYMENT IN JAVA ISLAND - Sutrisno; Sumaryoto, Sumaryoto; Sutrisno, Sutrisno (Yayasan Education and Social Center, 2025)
The research was conducted in Java Island by analyzing data from provincial districts/cities in Java Island on inflation, interest rates, rupiah exchange rates, total export-import, labor wage values, transportation infrastructure, and foreign portfolios on foreign direct investment (FDI) in Java Island, as well as GRDP and employment opportunities in the period 2013 to 2022. The population of this study is all provinces in Indonesia (38 provinces) as cross section data. While the time series data is 56 years (since the new order). While the sample of this study is panel data of 6 provinces in Java Island within 10 years. Where time series data will be taken from 2013-2022 and cross section data for 6 provinces which are the largest industrial estate locations in each province. This research method uses a descriptive verification method. The variables used are divided into two (2), namely the dependent variable and the independent variable. The dependent variable in this study is FDI (in the structure of research model 1) and GRDP and employment opportunities (in the structure of research model 2) while the independent variables in this study are logistics performance index, rupiah exchange rate, labor wages, inflation and infrastructure (in the structure of research model 1) and FDI (in the structure of research model Foreign direct investment (FDI) has a significant and positive effect on gross regional domestic product (GRDP t-1) on the island of Java by 83.68%. Meanwhile, foreign direct investment (FDI) has an insignificant and positive effect on employment opportunities on the island of Java.